Longitudinal monitoring of KRAS-mutated circulating tumor DNA enables the prediction of prognosis and therapeutic responses in patients with pancreatic cancer. - Fumiaki Watanabe; Koichi Suzuki; Sawako Tamaki; Iku Abe; Yuhei Endo; Yuji Takayama; Hideki Ishikawa; Nao Kakizawa; Masaaki Saito; Kazushige Futsuhara; Hiroshi Noda; Fumio Konishi; et al. (PLoS ONE)
Background Liquid biopsies enable the detection of circulating tumor DNA (ctDNA). However, the clinical significance of KRAS-mutated ctDNA for pancreatic cancer has been inconsistent with respect to its prognostic and predictive potential. Methods and findings A total of 422 blood samples were collected from 78 patients undergoing treatments for localized and metastatic pancreatic ductal adenocarcinoma. KRAS mutation in tissues and KRAS ctDNA levels in plasma were determined by RASKET and droplet digital polymerase chain reaction. Longitudinal monitoring of KRAS ctDNA was performed to assess its significance for predicting recurrence and prognosis and for evaluating therapeutic responses to chemotherapy compared with carbohydrate antigen 19-9 (CA19-9). In 67 tumor tissues, discrepancies in point mutations of KRAS were rarely observed among individual patients, implying that one targeted point mutation of KRAS can be determined in tumor tissues prior to longitudinal blood monitoring. One-time blood assessment of KRAS-mutated ctDNA before surgery or chemotherapy was not clearly associated with recurrence and prognosis. Sequential blood monitoring was performed in 39 patients who underwent surgery for potentially resectable tumors. Increased CA19-9 levels were significantly associated with recurrence, but not prognosis (P<0.001, P = 1.0, respectively), whereas emergence of KRAS ctDNA was significantly associated with prognosis (P<0.001) regardless of recurrence. Furthermore, in 39 patients who did not undergo surgery, detection of KRAS ctDNA was a predictive factor for prognosis (P = 0.005). Multivariate analysis revealed that detection of KRAS ctDNA was the only independent prognostic factor regardless of tumor resection (hazard ratios = 54.5 for patients who underwent surgery and 10.1 for patients who did not undergo surgery; P<0.001 for both). Patients without emergence of KRAS ctDNA within 1 year after surgery showed significantly better prognosis irrespective of recurrence (P<0.001). No detection or disappearance of KRAS ctDNA within 6 months of treatment was significantly correlated with therapeutic responses to first-line chemotherapy (P<0.001). Changes in KRAS status provided critical information for the prediction of therapeutic responses. Conclusions Our study showed for the first time that detection of KRAS ctDNA levels within a short period enables the prediction of prognosis and therapeutic responses in patients with pancreatic cancer.